In Vivo Evaluation of DMSA-Coated Magnetic Nanoparticle Toxicity and Biodistribution in Rats: A Long-Term Follow-Up - Fernanda Paulini; Aline R. M. Marangon; Carolina L. Azevedo; Juliana L. M. Brito; Marcelle S. Lemos; Marcelo H. Sousa; Fabiane H. Veiga-Souza; Paulo E. N. Souza; Carolina M. Lucci; Ricardo B. Azevedo (Nanomaterials, 2022)
This work presents a long-term follow-up (300 days) of rats after a single intravenous injection of DMSA-coated magnetite nanoparticles (DMSA-MNP). The animals were systematically evaluated by hematological, biochemical, and ultrasound examinations, monitoring the same animal over time. In addition, oxidative stress evaluation, DMSA-MNP biodistribution, computerized tomography for ex vivo organs, and histopathology analysis were performed at the end of the experiment period. Overall, DMSA-MNP administration did not cause serious damage to the rats’ health over the course of 300 days post-administration. All animals presented hematological parameters within the normal limits, and no alterations on serum creatinine, urea, ALT, and AST were related to DMSA-MNP administration. Liver and spleen showed no important alterations in any of the examinations. The kidneys of treated animals displayed intermittent pelvis dilation at ultrasound analysis, but without damage to the organ parenchyma after 300 days. The lungs of treated animals presented a light interalveolar septal thickening, but the animals did not present any clinical respiratory symptom. Nanoparticles were not detected in the vital organs of treated animals 300 days after administration. This work represents the first assessment of the long-term effects of DMSA-MNP and goes a step further on the safety of its use for biomedical applications.